2011
DOI: 10.19030/jabr.v18i4.2130
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach To Risk Management For Accounting Firms

Abstract: <p class="MsoBodyText" style="line-height: normal; margin: 0in 0.5in 0pt;"><span style="font-family: &quot;Times New Roman&quot;,&quot;serif&quot;; font-size: 10pt; mso-bidi-font-style: italic;">This paper develops an integrated risk management decision framework that provides insights into the many factors that are involved in controlling and managing risk for accounting firms.<span style="mso-spacerun: yes;">&nbsp; </span>Borrowing from the areas of insurance econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This research can fill the gap with research conducted by [4], and [5]. [4] research focuses more on CPA Firm business risk management and has an approach from several disciplines, so its scope is comprehensive. While the research by [5] only considers client acceptance as the key to controlling engagement risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This research can fill the gap with research conducted by [4], and [5]. [4] research focuses more on CPA Firm business risk management and has an approach from several disciplines, so its scope is comprehensive. While the research by [5] only considers client acceptance as the key to controlling engagement risk.…”
Section: Resultsmentioning
confidence: 99%
“…To design risk management in CPA Firm, [4] develop a framework for risk management using a multidisciplinary approach. In their research, [4] is more focused on CPA Firms' business risks, so the risks identified are services provided by CPA Firms, clients, service users, law, and CPA Firm businesses in general [4]. [5] conducts research on risk management in client acceptance.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation